2018
DOI: 10.1002/lary.27452
|View full text |Cite
|
Sign up to set email alerts
|

Incidental mastoid effusion diagnosed on imaging: Are we doing right by our patients?

Abstract: Objectives/Hypothesis To investigate whether radiologist‐produced imaging reports containing the terms mastoiditis or mastoid opacification clinically correlate with physical examination findings of mastoiditis. Additionally, to investigate whether and how often otolaryngology was unnecessarily consulted and inappropriate antibiotic therapy was initiated. Study Design Retrospective chart review within a large community hospital setting. Methods A retrospective review of 160 patients who had imaging tests perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Although exclusion of these studies caused an insignificant change to the pooled prevalence (9.3%, 95% CI 4.3–16.0), this analysis served to highlight potential study characteristics that may be of interest in our moderator analysis. Sayal et al 12 and Polat et al 21 both reported the smallest IMO rates out of all the studies, 0.1% and 1.4%, respectively. The factors that both studies had in common were that they contained the largest sample sizes, n = 205,792 and n = 29,850, respectively, and both inspected radiology reports to detect IMO.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Although exclusion of these studies caused an insignificant change to the pooled prevalence (9.3%, 95% CI 4.3–16.0), this analysis served to highlight potential study characteristics that may be of interest in our moderator analysis. Sayal et al 12 and Polat et al 21 both reported the smallest IMO rates out of all the studies, 0.1% and 1.4%, respectively. The factors that both studies had in common were that they contained the largest sample sizes, n = 205,792 and n = 29,850, respectively, and both inspected radiology reports to detect IMO.…”
Section: Resultsmentioning
confidence: 89%
“…There was a large difference in prevalence between studies that measured IMO by screening radiology reports 11,12,21–23,25,31 (3.5%, 95% CI 1.3–6.6) and directly evaluating radiological images 10,20,24,26–30 (14.5%, 95% CI 9.9–19.8), as shown in Figure 7. This difference was highly significant (QM (1) = 16.0, P < .0001) and contributed to the observed heterogeneity ( R 2 = 28.0%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On MR images, high signal intensity of T2 or T2 fluid-attenuated inversion recovery (FLAIR) imaging in the mastoid air cell cavity indicated ME (Fig. 1) 12,22) . Two independent reviewers confirmed these diagnoses.…”
Section: Methodsmentioning
confidence: 99%